Strategi Creative Branding Hijack Sandals untuk Meningkatkan Brand Image - Ilham Akbar Zam Zamy; Dadi Ahmadi (Jurnal Riset Public Relations, 2023)
Abstract.Hijack Sandals is a fashion brand that was born in Bandung in 2010 which until now is still very consistent in selling products that focus on footwear, namely sandals. They were born and appeared in that year because of the concern of the people around them, who made the shoes very comfortable. In fact, the climate in Indonesia is suitable for wearing sandals. Hijack Sandals has dozens of products filled with various kinds of sandals with different motifs and colors. This research is entitled "Creative Branding Hijack Sandals Strategy to Improve Brand Image (Case Study Regarding Hijack Sandals Creative Branding Strategy in Sustain the Culture Collection via Instagram)". The purpose of this research is to find out how Hijack Sandals' Creative Branding Strategy is in the Sustain the Culture collection and also what makes this research unique is that Hijack Sandals continues to consistently echo this campaign so that the sandal culture in this country never stops and is packaged as attractively as possible by creating content-content posted on Hijack Sandals Instagram. This research uses a case study approach that aims to find out how the strategy of Hijack Sandals' creative team in promoting the Sustain the Culture collection to improve Brand Image. Supporting data in this study is the presence of two key informants and two supporting informants. Founder and Creative Director as key informants, and supporting informants are followers of Hijack Sandals' Instagram account. Abstrak.Hijack Sandals adalah salah satu brand fashion yang lahir di Bandung pada tahun 2010 yang sampai saat ini masih sangat konsisten menjual produk berfokus pada alas kaki yaitu sandal. Mereka lahir dan muncul di tahun itu atas keresahan orang-orang sekitar yang sangat banyak membuat sepatu padahal sejatinya iklim di Indonesia itu cocok dengan memakai sandal. Hijack Sandals memiliki puluhan produk yang diisi oleh berbagai macam sandal dengan motif dan warna yang berbeda-beda. Penelitian ini berjudul “Strategi Creative Branding Hijack Sandals Untuk Meningkatkan Brand Image (Studi Kasus Mengenai Strategi Creative Branding Hijack Sandals Pada Koleksi Sustain the Culture melalui Instagram)”. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana Strategi Creative Branding Hijack Sandals pada koleksi Sustain the Culture melalui Instagram, yang menjadikan penelitian ini unik adalah Hijack Sandals terus konsisten menggaungkan campaign ini agar budaya bersandal di negara ini tidak pernah berhenti dan mereka kemas dengan semenarik mungkin dengan pembuatan konten-konten yang dimuat di Instagram Hijack Sandals. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus yang bertujuan untuk mencari tahu bagaimana strategi tim kreatif Hijack Sandals melakukan promosi pada koleksi Sustain the Culture untuk meningkatkan Brand Image. Data pendukung dalam penelitian ini adalah dengan adanya dua key informan dan satu informan pendukung. Founder dan Creative Director sebagai key informan, dan informan pendukung adalah followers akun Instagram Hijack Sandals.